High-throughput drawing and testing of metallic glass nanostructures. Issue 9 (22nd February 2017) - Hasan, Molla; Kumar, Golden
Abstract : We demonstrate high-throughput fabrication and mechanical testing of assembled nanostructures by controlling the extensional flow of metallic glass forming liquids. Abstract : Thermoplastic embossing of metallic glasses promises direct imprinting of metal nanostructures using templates. However, embossing high-aspect-ratio nanostructures faces unworkable flow resistance due to friction and non-wetting conditions at the template interface. Herein, we show that these inherent challenges of embossing can be reversed by thermoplastic drawing using templates. The flow resistance not only remains independent of wetting but also decreases with increasing feature aspect-ratio. Arrays of assembled nanotips, nanowires, and nanotubes with aspect-ratios exceeding 1000 can be produced through controlled elongation and fracture of metallic glass structures. In contrast to embossing, the drawing approach generates two sets of nanostructures upon final fracture; one set remains anchored to the metallic glass substrate while the second set is assembled on the template. This method can be readily adapted for high-throughput fabrication and testing of nanoscale tensile specimens, enabling rapid screening of size-effects in mechanical behavior.